Philippine sociology in the nineteen eighties a review. - Talledo, Tomasito (1993.)
This paper reviews the state of the Philippine sociology in the nineteen eighties through a critical and thematic reading of articles in the Philippine Sociological Review published in this decade (1980-1989). The categories and themes present in these articles are examined in this review against the backdrop of functionalism, a perspective considered dominant in the history of Philippine sociology, and vis-a-vis the social events which transpired in Philippine society during this decade. The review found out that towards the end of this decade, particularly on the areas of theory and political economy, sociological writings already departed from the influence of functionalism. The review concludes with a proposal for Filipino sociologists to reimagine their tasks by pushing the theoretical frontiers of the discipline, by exploring possible contributions from other discourses and by accepting the challenge of an emancipatory sociology.
Thesis (Graduate, Master of Arts in Sociology) Graduate School, College of Social Sciences and Philosophy, University of the Philippines, Diliman, Quezon City.
Keywords: Philippine Sociology